Analisis Perbedaan Pemahaman Antara Experienced dan Non-Experienced Smartphone User Terhadap Application Permission - Fairuz Risky Yusniasari; Ari Kusyanti; Aryo Pinandito (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Application Permission is an application licensee type which appears before to installation process or update an application in smartphone. Many applications states that the permissions were installed to take some personal information of smartphone user. Smartphone user will be divided into two levels. Experienced smartphone user have tendency for not provide their personal information. While non-experienced smartphone user have tendency for provide their personal information. This research aims to analyze the difference understanding between the experienced and non-experienced smartphone users. It will analyze, what is the difference understanding between the experienced and non-experienced smartphone user towards installation process or update. Data collected from 200 Android user. The method that is used for analyzing is Independent Sample T-test and Regression Linear. The result of research is that there is significant difference understanding between experienced and non-experienced smartphone user.